A case study on determinants of human resource practices influencing retention of employees in Kedah State Development Corporation, Malaysia - Sanjeevkumar, Virmala; Wei, Wang (Maryland Institute of Research (MIR), 2012)
In order to succeed and prosper in the intensive competitive environment; organizations need to maintain a competitive labor force and try to stimulate them to perform well. Organizations holding effective labor force have a better chance to win in the business. In modern business, many organizations are bearing employee's, knowing how to maintain employees to stay in the organization is wiser than to prevent them from quitting jobs. For the retention is a proactive action to keep good workforce, while preventing employee turnover is a reactive active to avoid loss. This research will explore the influence of the 5 factors (compensation, work-life balance, organizational commitment, career opportunity and supervisor support) on employees' intention to stay in the Kedah State Development Corporation Company, what are the possible attractive factors for them to stay there. This study will combine both theoretical and empirical research, trying to find factors that affect employees' retention decision. These factors can be used as options for other organizations. So other organizations may take these factors into consideration when they want to keep their labor force and maintain effective employees for the organization. This research will investigate the main factor which causes employee retention in KSDC and why employees are preferred to stay in the KSDC.